2015
DOI: 10.1007/s11356-014-4021-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the concentrations and distribution of carbonyl compounds in selected areas of a Brazilian bus terminal

Abstract: This study describes the determination of 30 carbonyl compounds (CCs) in three areas (bus boarding platform, passenger circulation area, and a pastry shop) of the Presidente João Goulart Bus Terminal, located at Niterói City, RJ, Brazil, and in an open area 700 m distant from the terminal. Samples were collected using SEP-PAK cartridges impregnated with 2,4-dinitrophenylhydrazine, during May to July 2012. The hydrazones formed were analyzed using rapid resolution liquid chromatography with UV detection. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Samples taken from the pastry shop of a bus terminal area showed significant concentrations of formaldehyde, although acetaldehyde predominated. The authors suggest that such results depend on the activities carried out inside the pastry shop, related to food preparation [ 27 ]. In this regard, a recent hypothesis is that formaldehyde and acetaldehyde exposure occurs in bakeries and pastry industries particularly in processes that involve a strong leavening [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples taken from the pastry shop of a bus terminal area showed significant concentrations of formaldehyde, although acetaldehyde predominated. The authors suggest that such results depend on the activities carried out inside the pastry shop, related to food preparation [ 27 ]. In this regard, a recent hypothesis is that formaldehyde and acetaldehyde exposure occurs in bakeries and pastry industries particularly in processes that involve a strong leavening [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent case–control study, excess risks were found for ever exposure to welding fumes, organic solvents, hexavalent chromium (Cr(VI)), leather dust, and nickel [ 24 ]. In previous studies, the most reported cases of chromium-induced nasal cancer were squamous cell carcinoma [ 27 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Formaldehyde and AA can be emitted directly from the source or by secondary production via photochemical reactions (Chi et al, 2007; de Carvalho et al, 2008; de Mendonça Ochs et al, 2015; Ho et al, 2016; Morknoy et al, 2011; Wang et al, 2005). Emissions sources include vegetation and anthropogenic sources such as gas stations, motor vehicle emissions, and bus terminals (Anderson et al, 1996; de Mendonça Ochs et al, 2015; Duan et al, 2012; Lü et al, 2010; Morknoy et al, 2011; Nogueira et al, 2014; Nogueira et al, 2017; Viskari et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Emissions sources include vegetation and anthropogenic sources such as gas stations, motor vehicle emissions, and bus terminals (Anderson et al, 1996; de Mendonça Ochs et al, 2015; Duan et al, 2012; Lü et al, 2010; Morknoy et al, 2011; Nogueira et al, 2014; Nogueira et al, 2017; Viskari et al, 2000). Concentrations of these species have been reported to depend on meteorological conditions such as temperature, humidity, and wind speed (Lü et al, 2016; Missia et al, 2010; Morknoy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation